THE INFLUENCE OF BRAND IMAGE, PRICE, PRODUCT QUALITY AND PERCEIVE RISK ON PURCHASE DECISION TRANSFORMER PRODUCT PT. SCHNEIDER INDONESIA - Rizan, Mohammad; Nauli, Muthya Octariany; Mukhtar, Saparuddin (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The aim of this objective reserach is to find a picture of the influence of brand image, price, product quality and perceive risk on purchase decision transformer product PT. Schneider Indonesia for business consumers in Indonesia. This research is quantitative study with descriptive and causal method undertaken at PT. Schneider Indonesia business unit transfomer in 2013. Data collection done towards 97 respondents and its surrounding others industries segment. The data were collected with questonnaire and analyzed with SPSS ver. 20.0. The results of this study concluded that (1) the brand image positive and has significant impact on purchasing decisions, (2) Price positive and has significant impact on purchasing decisions, (3) product quality positive and has significant impact on purchasing decisions, (4) perceive risk positive and significant impact on purchasing decisions and (5) all of the independent variables (brand image, price, product quality, and perceive risk) have significant positive effect on the dependent variable (purchase decisions). The variables that most influence the purchase decision is price variable, the second is brand image, the third is perceive risk and the fourth is a product quality. Keywords: brand image, price, product quality, perceive risk and purchase decision